Maria Valéria Rezende: sabem vocês o que é ser um canal? - Demasi, Maria Antonia (2022)
This research was guided by the desire to navigate through Maria Valéria Rezende’s literature, her characters and stories of life and death, to have glimpses into potential old age experiences and transform one’s own experience into life power, a space of construction of worlds and ways of existence. The presence of old women and men in the author’s literary work is investigated from the perspective of her work being an intricate life-text about aging. Therefore, a transforming relationship substantiates the backbone of this dissertation. Both the researcher and the researched are involved and merge in an encounter that triggers new becomings— according to the concept informed by Deleuze and Guattari. Wherefore, a methodological course with close contact was followed for over a year, recording free conversations in audios and videos. Reading her work, recording stories and detailed observations of places and objects that surround Maria Valéria Rezende and carry memories were the preferred methods until the Covid-19 pandemic (Sars-Co-2 2020), which forced a change in the methodological approach to either telephone calls or videoconferences. Literature as a mirror of a myriad of old age experiences brought about by Maria Valéria Rezende in her writing-life—her vast literary production and missionary experiences of struggle alongside poor and social excluded population—are foundations to refuse aging as it is currently forged as a product by values, discourses, and social, political, and cultural organizations